Studies on gasoline fuel processor system for fuel-cell powered vehicles application - Moon, DJ; Sreekumar, K; Lee, SD; Lee, BG; Kim, HS (ELSEVIER SCIENCE BV, 2001)
Hydrogen generation for fuel-cell powered vehicles by reforming technologies from various fuels has gained much attention recently. The successful development of a fuel cell-powered vehicle is dependent on the developement of a fuel processor. As part of the development of gasoline reforming system for intergration with PEM fuel cell, we investigated POX reforming (or autothermal reforming, ATR) reaction of iso-octane with/without 100 ppm sulfur and of reformulated naphta over a commercial naphta reforming (NRC) catalyst. We also investigated high temperature water gas shift (HTS) reaction over Fe3O4-Cr2O3 catalysts and low temperature shift (LTS) reaction over Cu/ZnO/Al2O3 catalyst to remove CO from the hydrogen-rich stream produced by fuel processing section. The H-2 and CO concentrations from the POX reforming of iso-octane over the NRC catalyst increased with increasing reaction temperature, while that of CO2 and CH4 decreased. It was found that the NRC catalyst was prone to be poisoned by sulfur contained in gasoline, but there is no coke deposition at 700 degreesC under the tested conditions. We confirmed that the concentration of CO in hydrogen-rich stream is reduced to <3000 ppm as the exit gas of gasoline POX reforming over naphta reforming catalyst was passed through HTS and LTS reactors. In order to reduce the concentration of CO in hydrogen-rich stream of LTS reactor, a preferential partial oxidation (PROX) reactor and new high-performance catalysts with sulfur- and coke-resistance will be needed. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: GAS